Synthesis of 5‐Phosphonoisoxazoline N‐Oxides by Selective O‐Alkylation of Nitronate Anions. Issue 2 (20th November 2015) - Perez, Vincent; Rabasso, Nicolas; Fadel, Antoine
Abstract: A series of 5‐phosphonoisoxazoline N ‐oxides were prepared in good to excellent yields by selective O ‐alkylation of nitronate anions with (α‐tosyloxyvinyl)phosphonates. A comprehensive study was undertaken to limit the competitive formation of the (β‐nitrocyclopropyl)phosphonate resulting from C ‐alkylation of the ambident nitronate anions. The 5‐phosphonoisoxazoline N ‐oxides thus formed were reduced to the corresponding 5‐phosphonoisoxazolines. Abstract : 5‐Phosphonoisoxazoline N ‐oxides are prepared in good to excellent yields by selective O ‐alkylation of nitronate anions with (α‐tosyloxyvinyl)phosphonates. A comprehensive study is undertaken to limit the competitive formation of the (β‐nitrocyclopropyl)phosphonate resulting from C ‐alkylation of the ambident nitronate anions. Ts = para ‐tolylsulfonyl, DBU = 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene.